2016
DOI: 10.1177/1557988316668131
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Testicular Cancer and Self-Examination Among Northern Irish Males

Abstract: Testicular cancer incidence rates are increasing worldwide making it the most common malignancy in males aged 15 to 45 years. Without a known way to prevent the disease health professionals must promote awareness and early detection. A literature review identified a scarcity of information regarding awareness and knowledge of, and attitudes toward, testicular cancer and testicular self-examination among men in Northern Ireland. This study aimed to establish baseline data for Northern Ireland using a convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 33 publications
5
60
1
6
Order By: Relevance
“…Hence, a major part of the endeavor to increase detection must rely on public education to raise personal awareness. A study that was conducted in Northern Ireland found that only 17% of men within the at-risk age range had heard of a testicular self-examination, suggesting the urgent need for a more aggressive promotion of awareness by the health care system [23]. When considering that the United Kingdom has one of the lowest MIRs at 0.03, one can only imagine the scarcity of personal awareness promotion programs and education that are provided in countries with high MIRs.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a major part of the endeavor to increase detection must rely on public education to raise personal awareness. A study that was conducted in Northern Ireland found that only 17% of men within the at-risk age range had heard of a testicular self-examination, suggesting the urgent need for a more aggressive promotion of awareness by the health care system [23]. When considering that the United Kingdom has one of the lowest MIRs at 0.03, one can only imagine the scarcity of personal awareness promotion programs and education that are provided in countries with high MIRs.…”
Section: Discussionmentioning
confidence: 99%
“…In Northern Ireland, males aged 18-45 years, also falsely recognized TC risk factors, i.e. specifying body weight (44% of respondents) or alcohol drinking (21% of respondents) [14]. Unfortunately, the awareness of cryptorchidism, which is a wellknown risk factor for testicular cancer, was unsatisfying among our study population.…”
Section: Discussionmentioning
confidence: 73%
“…'Movember', which subsidized over 1,200 projects in about 20 countries. The projects were aimed at early detection of cancer, promotion of self-examination practices, and implementation of effective treatments [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Cryptorchidism, also referred to as maldescended testis, is the failure of descent of one or both of the testes into the scrotum and is a common clinical diagnosis in newborn boys and one of the strongest risk factors for infertility and testicular cancer [33][34][35]. Approximately 10% of all cases of testicular tumors occur in boys with a history of cryptorchidism [36].…”
Section: Risk Factorsmentioning
confidence: 99%
“…TC is associated with a family history link as well [33][34][35]. Men, who have a firstdegree relative with testicular cancer, have a reasonably increased risk [39].…”
Section: Risk Factorsmentioning
confidence: 99%